Immunodiagnosis of swine cysticercosis by indirect ELISA employing a heterologous antigen from Taenia crassiceps metacestode - Biondi, Germano Francisco [UNESP]; Mucciolo, R. G.; Nunes, Caris Maroni [UNESP]; Richtzenhain, L. J. (Elsevier B.V., 1996)
C. Larralde et al. (1990, Arch. Pathol. Lab. Med., 114:926-928) demonstrated that heterologous antigen from the laboratory-adapted murine Taenia crassiceps metacestode may substitute those from Taenia solium in the immunodiagnosis of human cysticercosis by the indirect enzyme-linked immunosorbent assay (IE). ?This antigen is easily obtained at a laboratory level and solves the problem of T. solium cysticerci collection from naturally or experimentally infected swine. In this study an IE employing a heterologous antigen from the T. crassiceps metacestode was evaluated for the immunodiagnosis of swine cysticercosis. Sera from 300 swine free of T. solium cysticerci by post-mortem examination were employed to determine two IE cut- off values: 1) Mean ELISA values + 2 standard deviations (2 sigma cut-off) and 2) - Mean ELISA values + 3 standard deviations (3 sigma cut-off). The specificity of IE was 97% with the 2 sigma cut-off and 100% with the 3 sigma cut-off. When applied to ten sera from swine infected by cysticerci of T. solium by post-mortem examination, the sensitivity of IE was 100% independent of the cut off.
Keywords: swine cysticercosis; immunodiagnosis; indirect ELISA; heterologous antigen; Taenia crassiceps